Flores do abismo, imagens do inconsciente [2012] - Dionisio, Gustavo Henrique [UNESP] (My University, 2013)
Presented in a rehearsal form, this article aims to bring out a historical discussion about the relationship between art-madness in Brazil. Result of a research that had as object the critical fortune written on the first exhibit of the Museum of Images of the Unconscious, this work aims to connect two little closer fields: art criticism and mental health, especially since Mário Pedrosa’s work. It was possible to ascertain, throughout the investigation, that there was a position taken by art critics at that time (the 1940s), that position is basically divided into two, briefly explored here: those who encouraged the exhibits, and thereby attested the artistic value of the work produced in the studio of Pedro II Psychiatric Center (where it was founded the Museum); and those who decried the artistic character of "unconscious images", as would be known the works that were produced there. Thus, we can say that, indeed, the virgin art – so entitled by Pedrosa – functioned as a kind of sting to the renewal of our health practices, but mainly influenced the completion of a cycle of modernism in our country.

Apresentado sob a forma de ensaio, este artigo pretende trazer à tona uma discussão histórica acerca da relação arte-loucura no Brasil. Fruto de pesquisa que teve como objeto a fortuna crítica escrita sobre as primeiras exposições do Museu de Imagens do Inconsciente, este trabalho almeja articular dois campos de pouca aproximação: crítica de arte e saúde mental, sobretudo a partir do trabalho de Mário Pedrosa. Foi possível averiguar, ao longo da investigação, que houve um posicionamento assumido pelos críticos de arte àquela época (década de 1940), posição que se dividia basicamente em duas, aqui brevemente exploradas: daqueles que incentivavam as exposições, e desse modo atestavam o valor artístico dos trabalhos produzidos no ateliê do Centro Psiquiátrico Pedro II (onde fora inaugurado o Museu); e a daqueles que censuravam o caráter artístico das “imagens do inconsciente”, como ficariam conhecidas as obras ali produzidas. Desse modo, podemos dizer que, com efeito, a arte virgem – assim intitulada por Pedrosa – funcionou como uma espécie de aguilhão para a renovação de nossas práticas em saúde, mas influenciariam, sobretudo, na finalização de um ciclo do modernismo em nosso país.
Keywords: Virgin art; Art criticism; Psychology art; Mental health; Unconscious images; Arte virgem; Crítica de arte; Psicologia da arte; Saúde mental; Imagens do inconscient